Incidence of respiratory syncytial virus infection in children with congenital heart disease undergoing immunoprophylaxis with palivizumab in Pará state, north region of Brazil - Roseane Porfírio de Souza; Andre Luis Ribeiro Ribeiro; Sílvio Augusto Fernandes de Menezes; Luiz Fernando Almeida Machado (BMC, 2019)
Abstract Background Palivizumab prophylaxis for the human respiratory syncytial virus (HRSV) has been reported to reduce the risk of hospital admissions related to HRSV in children with congenital heart disease (CHD). These children are at high risk of developing severe lower respiratory tract infection (LRTI) due to HRSV infection. Our goal was to evaluate the incidence of HRSV infection in children with CHD after being submitted to immunoprophylaxis with palivizumab in Pará state, North region of Brazil. Methods A prospective and observational cohort study was performed in children ≤2 years of age with CHD who received palivizumab immunoprophylaxis between January 1 and June 31, 2016. A questionnaire about basic non-medical care measures was applied to parents/legal representatives. Data on patients' demographic characteristics, household environment, and respiratory infections were evaluated. HRSV infection was determined by qPCR. Results There were 104 children enrolled in this investigation and the results showed a mean age of 10.6 months, an average weight of 7.3 kg and 3.5 doses of palivizumab per children during seasonality of HRSV. Respiratory infection was observed in 27.9% of cases, of which 9.6% were LRTI. No case of children who received palivizumab immunoprophylaxis and developed influenza-like symptoms tested positive for HRSV. Conclusion Although the lack of a control group doesn't allow to affirm the effectiveness of HRSV passive immunization, the immunoprophylaxis with palivizumab appeared to be totally efficient in preventing respiratory infection by HRSV in children up to two years of age with CHD.